The energy policy in Spain: the case of the sector of the electricity - Antonio Sаnchez-Andrés (Ибероамериканские тетради)
In this article the recent electricity policy in Spain is analysed. Firstly, the paper study how the goals were established, afterword it explains the design of the economic policy and ﬁnally their results are hi-ghlighted. The article concludes by evaluating the results obtained, with reference to the initially established objectives and also the costs of the policies implemented